2004
DOI: 10.4049/jimmunol.172.7.4535
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Gene Delivery of Elafin and Secretory Leukocyte Protease Inhibitor Attenuates NF-κB-Dependent Inflammatory Responses of Human Endothelial Cells and Macrophages to Atherogenic Stimuli

Abstract: Atherosclerosis is a chronic inflammatory disease affecting arterial vessels. Strategies to reduce the inflammatory responses of endothelial cells and macrophages may slow lesion development and prevent complications such as plaque rupture. The human protease human neutrophil elastase (HNE), oxidized low density lipoprotein, LPS, and TNF-α were chosen as model stimuli of arterial wall inflammation and led to production of the chemokine IL-8 in endothelial cells. To counteract the activity of HNE, we have exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 64 publications
6
121
0
Order By: Relevance
“…However, it is worth noting that NE regulation of the inflammatory response is cell content dependent. Different studies showed that NE increases IL‐8 in endothelial cells,44 while NE suppresses IL‐8 expression in SMCs 45. Evidence has also suggested that NE may function as a negative regulator of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that NE regulation of the inflammatory response is cell content dependent. Different studies showed that NE increases IL‐8 in endothelial cells,44 while NE suppresses IL‐8 expression in SMCs 45. Evidence has also suggested that NE may function as a negative regulator of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the antiinflammatory effects of the anti-leukoproteinases may involve inhibition of NFKB. In vitro, overexpression of SLPI suppresses NFKB activation (Jin et al 1997, Sano et al 2003, Henriksen et al 2004. It can prevent proteosome-dependent IkBb degradation (Lentsch et al 1999) and also directly bind to NFKB consensus sites on DNA, inhibiting transcription (Taggart et al 2005).…”
Section: Natural Antimicrobial Peptides (Naps)mentioning
confidence: 99%
“…mRNA expression (data not shown). Intracellular SLPI is known to inhibit TLR 4 signaling by suppressing the activation of NF-B by preventing the degradation of the inhibitory factor IB (32,36,37). To see whether SLPI is involved in suppression of cellular activation in DCs, we compared the level of NF-B p65 activation in LPS-stimulated WT and SLPI Ϫ/Ϫ BM-DCs.…”
Section: Mhciimentioning
confidence: 99%